PENGARUH FEEDBACK DAN FEED-FORWARD DALAM MEMBANGUN KAPABILITAS MARKET ORIENTATION & ENTREPRENEURSHIP DAN ORGANIZATIONAL PERFORMANCE - Neng Asiah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
he purpose of this study are to determine the effect of feedback control, feed-forward control on themarket orientation and entrepreneurship, the effect of market orientation on organizational capabilities andinfluence the ability of entrepreneurship performance to organizational performance. The population of this study are all managers of manufacturing companies in the City and County ofBekasi. The sampling technique used was purposive sampling. The respondents of this study are middlemanagers. This study uses the approach of Structural Equation Model (SEM) using software Partial LeastSquare (PLS). PLS is a structural equation modeling (SEM) based components or variant (variance). The results are feed-back control has positive effect on market orientation, this is consistent withresearch Graftonet al. (2010). And feed-back control also positively effect to Entrepreurship, this is concurswith research Graftonet al. (2010). the use of PMS interactively / feed-forward control has positive effect onboth market orientation and entepreneurship, this is consistent with Henri (2006). Market orientation has positifeffect to organizational performance, this is consistent with the study of Graftonet al. (2010). Entrepreneurshiphas positive affects to organizational performance, this is consistent with the study of Graftonet al. (2010)